Return on investment analysis and its applicability to community disaster preparedness activities: Calculating costs and returns. (December 2019) - Kousky, Carolyn; Ritchie, Liesel; Tierney, Kathleen; Lingle, Brett
Abstract: Return on investment (ROI) analysis is a tool traditionally used in the private sector to evaluate and compare projects and investments. Over the past several decades, the use of ROI analysis has expanded to include a broader array of social and environmental benefits; this is termed social return on investment, or SROI. This paper examines the use of SROI analysis to evaluate investments in disaster preparedness. The paper outlines the basic methods and then discusses several challenges to using SROI in this context: the difficulty identifying all returns, especially spillover benefits; the challenge of separating attribution from contribution; the resources required to value nonmarket inputs and outcomes; the need to adequately address uncertainty; and the limitation of addressing distributional issues in SROI analysis. We explore these issues and the possibility of conducting an SROI of disaster preparedness activities in Tulsa, Oklahoma.